2010
DOI: 10.1152/jn.01092.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss Alters Serotonergic Modulation of Intrinsic Excitability in Auditory Cortex

Abstract: Sensorineural hearing loss during early childhood alters auditory cortical evoked potentials in humans and profoundly changes auditory processing in hearing-impaired animals. Multiple mechanisms underlie the early postnatal establishment of cortical circuits, but one important set of developmental mechanisms relies on the neuromodulator serotonin (5-hydroxytryptamine [5-HT]). On the other hand, early sensory activity may also regulate the establishment of adultlike 5-HT receptor expression and function. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Adaptation to the pronounced differences between the neural activation evoked by electrical stimulation and by physiological firing of inner hair cells consists of other significant processes that may take place during this period . Deafness is known to cause increased spontaneous activity, tonotopic distortion, homeostatic changes, and strengthening of non-auditory inputs in auditory cortex (Kral 2007;Rao et al 2010). It is likely that the time a cochlear implant recipient spends adapting to the device is a period of recovery from sensory deprivation rather than a protracted period required for learning to compensate for degraded speech.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation to the pronounced differences between the neural activation evoked by electrical stimulation and by physiological firing of inner hair cells consists of other significant processes that may take place during this period . Deafness is known to cause increased spontaneous activity, tonotopic distortion, homeostatic changes, and strengthening of non-auditory inputs in auditory cortex (Kral 2007;Rao et al 2010). It is likely that the time a cochlear implant recipient spends adapting to the device is a period of recovery from sensory deprivation rather than a protracted period required for learning to compensate for degraded speech.…”
Section: Discussionmentioning
confidence: 99%
“…In the gerbil LSO and the IC of mouse and Mexican free-tailed bat, agonists that activate this receptor type depress responsiveness to the electrical stimulation of input fibers or to auditory stimuli (Fitzgerald and Sanes, 1999; Hurley, 2006, 2007). There is also evidence for a post-synaptic site of serotonin-evoked suppression in the cortical slice preparation; application of serotonin decreases the spiking response and adaptation to injected current, and lowers the input resistance (Rao et al, 2010). Other mechanisms for suppression may be presynaptic.…”
Section: Physiological Effects Of Serotoninmentioning
confidence: 99%
“…This was true even though other receptor genes did not show these effects. Rao et al (2010) found similarly dramatic effects of sham surgical procedures in the auditory cortex. In their study, real and sham cochleotomies had similar effects on the ability of serotonin to decrease firing rates, input resistance, and spike rate adaptation.…”
Section: Discussionmentioning
confidence: 85%
“…Damage to the auditory system by trauma, aging, or peripheral deprivation can cause a myriad of molecular and physiological changes (Argence et al, 2006; Dong et al, 2010a,b; Holt et al, 2005; Manzoor et al, 2013; Mossop et al, 2000; Rao et al, 2010; Tadros et al, 2007; Vale and Sanes, 2002). These changes may be viewed as compensatory or even pathological, and could contribute to aberrant perceptual states such as tinnitus (Eggermont and Roberts, 2004; Knipper et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation